2008
DOI: 10.1016/j.biomaterials.2008.03.034
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional electrospun ECM-based hybrid scaffolds for cardiovascular tissue engineering

Abstract: Electrospinning using natural proteins or synthetic polymers is a promising technique for the fabrication of fibrous scaffolds for various tissue engineering applications. However, one limitation of scaffolds electrospun from natural proteins is the need to cross-link with glutaraldehyde for stability, which has been postulated to lead to many complications in vivo including graft failure. In this study, we determined the characteristics of hybrid scaffolds composed of natural proteins including collagen and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
304
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 415 publications
(310 citation statements)
references
References 52 publications
(64 reference statements)
3
304
0
3
Order By: Relevance
“…However, gelatin fibers exhibit higher tensile moduli than collagen fibers. Gelatin also exhibits excellent biodegradability, non-antigenicity, and cost efficiency; similar characteristics to electrospun collagen [44][45][46]. One of the major drawbacks of gelatin is that it dissolves as a colloidal sol at temperatures at or above 37 °C, and gels near room temperature.…”
Section: Gelatinmentioning
confidence: 98%
“…However, gelatin fibers exhibit higher tensile moduli than collagen fibers. Gelatin also exhibits excellent biodegradability, non-antigenicity, and cost efficiency; similar characteristics to electrospun collagen [44][45][46]. One of the major drawbacks of gelatin is that it dissolves as a colloidal sol at temperatures at or above 37 °C, and gels near room temperature.…”
Section: Gelatinmentioning
confidence: 98%
“…The combination of PCL with different natural polymers such as collagen, elastin and gelatin has revealed that electrospun PCL/gelatin scaffolds showed a higher tensile strength when compared to the other hybrid scaffolds according to Heydarkhan-Hagvall et al [79]. The effects of pore size on cell attachment and migration was determined by in vitro studies using adipose-derived stem cells culture, where cell migration into the scaffold was predominantly seen in the PCL/gelatin hybrid.…”
Section: Poly(ε-caprolactone)-based Scaffoldsmentioning
confidence: 99%
“…Moreover, it has low tensile strength (~23 MPa), but very high elongation at breakage (4700 %) making it a good elastic biomaterial [81] [182]. PCL is used in the production of implants composed of adhered nano/microspheres [183], electrospun fibers [184,185], or porous networks [186] used for regeneration of bone [187,188], ligament [189,190], cartilage [191], nerve [192], and vascular tissues [193]. In addition, PCL is often blended or copolymerized with other polymers like polyesters and polyethers to expedite overall polymer erosion [194].…”
Section: Polyestersmentioning
confidence: 99%